1990
DOI: 10.1007/bf00266407
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fiber typing in routinely processed skeletal muscle with monoclonal antibodies

Abstract: Muscle fiber typing is conventionally performed using mATPase enzyme histochemistry on cryostat sections. After pre-incubation of sections at pH 4.3, 4.6 and 10.3, based on the pattern of enzyme reactivity, the fibers can be classified in types I, II (subtypes A, AB and B) and the intermediate C (I and II) fibers. We have attempted to perform fiber typing of human psoas muscle by immunohistochemistry, using monoclonal antibodies R11D10 (specific for cardiac and type I skeletal myosin) and MY-32 (specific for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 12 publications
0
36
0
Order By: Relevance
“…MHC isoforms of skeletal muscle fibers correspond to certain types of muscle fibers determined by the ordinary enzyme histochemical classification [37,39,56,76,78,79] as shown in Figs. 1 and 2.…”
Section: Classical Identification Of Muscle Fibermentioning
confidence: 96%
“…MHC isoforms of skeletal muscle fibers correspond to certain types of muscle fibers determined by the ordinary enzyme histochemical classification [37,39,56,76,78,79] as shown in Figs. 1 and 2.…”
Section: Classical Identification Of Muscle Fibermentioning
confidence: 96%
“…The specificity and characterization of these mAbs against MHC isoforms have been previously established. The mAbs NOQ7-5-4D is specific to type I MHC (Narusawa et al, 1987;Petrof et al, 1992;Rubinstein and Hoh, 2000), MY-32 to all fast-type MHCs (Havenith et al, 1990;Monemi et al, 2000), SC-71 to type IIa MHC (Schiaffino et al, 1989;Stal et al, 1994;Monemi et al, 2000), ALD-58 to MHC-ton (Shafiq et al, 1984;, BA-G5 to MHC-␣ (Michel et al, 1996), F1.652 to MHC-emb (Michel et al, 1996), and N2.261 to MHC-neo (Michel et al, 1996).…”
Section: Immunocytochemistrymentioning
confidence: 99%
“…The MY-32 antibody (Havenith et al, 1990) has been shown to specifically identify type IIA and IIB muscle fibers. MY-32 immunoreactivity was localized to muscle fibers that were both parallel and perpendicular to the plane of the tissue (Fig.…”
Section: Newborn and Adult Tongue Muscles Are Composed Exclusively Ofmentioning
confidence: 99%
“…The MY-32 monoclonal antibody (Sigma Chemical Co., St. Louis, MO) has been shown to specifically label type II skeletal muscle fibers (Havenith et al, 1990). To attain a high-resolution image of MY-32-labeled thick filaments, the images were recorded photographically and the color print was scanned such that the contrast could be adjusted for printing on a Phaser 440 high-resolution color printer.…”
Section: Immunohistochemistrymentioning
confidence: 99%